(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The new agenda for Public Health in India encompasses several key components, including the epidemiological transition, demographical transition, environmental changes, and social determinants of health. To address these challenges effectively, there is a pressing need to revive primary health care based on the principles established at Alma-Ata in 1978. The government plays a pivotal role in shaping population health, not only within the healthcare sector but also through its influence on various other sectors. This article serves as a literature review, examining the existing governmental infrastructure for addressing public health needs in India, its achievements, limitations, and prospects for the future.